Hexagonal boron nitride powder for cosmetics, and cosmetics
The hexagonal boron nitride powder for cosmetics, characterized by a specific aspect ratio and oil absorption range, addresses the challenges of achieving balanced stretchability, transparency, and glossiness, resulting in improved cosmetic performance and ease of use.
Patent Information
- Application Number
- JP2023516358
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-19
- Filing Date
- 2022-03-22
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2042-03-22
AI Technical Summary
Hexagonal boron nitride powders for cosmetics face challenges in achieving balanced stretchability, transparency, and glossiness due to issues with particle size, aspect ratio, and oil absorption, which can lead to whitening, impaired glossiness, and difficulty in mixing with other components.
A hexagonal boron nitride powder with primary particles having an aspect ratio of 25 or less and an oil absorption amount of 50 to 90 mL/100 g, optimized to improve slipability, elongation, and transparency while maintaining a desirable glossiness and ease of mixing.
The optimized hexagonal boron nitride powder exhibits excellent stretchability and forms a cosmetic layer with superior transparency and glossiness, while also being easily mixable with other components, thus addressing the limitations of existing powders.
Smart Images

Figure 0007667854000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a hexagonal boron nitride powder for cosmetics, and to a cosmetic. [Background technology]
[0002] Hexagonal boron nitride has lubricity, high thermal conductivity, and insulating properties, and is used in various applications such as solid lubricants, release agents, fillers for resins and rubbers, raw materials for cosmetics, and heat-resistant insulating sintered bodies. Hexagonal boron nitride powder has functions such as improving the slipperiness, extensibility, and hiding power of cosmetics, as well as imparting gloss and other properties to cosmetics.
[0003] Talc powder, mica powder, and the like are used as extender pigments that can perform the same function as hexagonal boron nitride powder. However, since talc powder and the like are made from natural minerals, there is a large variation in particle size and thickness, and separate adjustments are required to produce cosmetics with stable quality. Hexagonal boron nitride powder allows adjustment of particle size, thickness, and the like, and further has superior slipperiness compared to talc powder and mica powder. Therefore, hexagonal boron nitride powder is often used in cosmetics that require superior slipperiness. Patent Document 1 proposes a hexagonal boron nitride powder in which the ratio of shear stress to applied pressure is within a specified numerical range in order to improve slipperiness.
[0004] The required properties for cosmetics are diverse, and the required properties for the raw material hexagonal boron nitride powder are also increasing. For example, Patent Document 2 proposes a hexagonal boron nitride powder for cosmetics with excellent thin film forming properties and improved cool feeling and transparency (bare skin feel), in which the hydrophilic functional groups on the surface are reduced and the oil absorption is increased. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-043792 A [Patent Document 2] JP 2014-094878 A Summary of the Invention [Problem to be solved by the invention]
[0006] In order to improve the spreadability, which is one of the usability of cosmetics, it is possible to reduce the particle size of the primary particles of hexagonal boron nitride, which is an extender pigment. However, when the particle size is reduced, the cosmetics containing hexagonal boron nitride powder may appear white due to light scattering, and the glossiness of the cosmetic layer may be impaired. In addition, in order to improve the transparency, it is preferable to provide a thin cosmetic layer on the skin. However, if the aspect ratio of the primary particles of hexagonal boron nitride is made too large to improve the transparency, the oil absorption increases, and it tends to be difficult to mix the hexagonal boron nitride powder with other ingredients when preparing the cosmetics. In addition, there may be cases where the original tactile feel of hexagonal boron nitride is impaired or the manufacturing process of the cosmetics becomes complicated due to the need for additional surface treatment or ingredient adjustment. From the viewpoint of achieving a good balance between spreadability, transparency, and glossiness when used as a cosmetic, there is room for improvement.
[0007] An object of the present disclosure is to provide a hexagonal boron nitride powder for cosmetics which has excellent elongation when used in cosmetics and gives the cosmetic layer excellent transparency and luster. [Means for solving the problem]
[0008] One aspect of the present disclosure provides a hexagonal boron nitride powder for cosmetics, which contains primary particles of hexagonal boron nitride, the primary particles having an aspect ratio of 25 or less, and an oil absorption of 50 to 90 mL / 100 g.
[0009] The hexagonal boron nitride powder for cosmetics has a primary particle aspect ratio within a specified range and a specific oil absorption, and therefore can be suitably used as a raw material for cosmetics. When used as a cosmetic, the hexagonal boron nitride powder can exhibit excellent extensibility and can form a cosmetic layer that exhibits excellent transparency and luster.
[0010] The hexagonal boron nitride powder has a BET specific surface area of 1.5 to 5.0 m 2 / g.
[0011] The hexagonal boron nitride powder has a tap density of 0.35 g / cm 3 It may be the following:
[0012] The hexagonal boron nitride powder may have a total oxygen content of 0.01 to 0.20 mass %.
[0013] One aspect of the present disclosure provides a cosmetic comprising the above-mentioned hexagonal boron nitride powder for use in cosmetics.
[0014] Since the cosmetic contains the above-mentioned hexagonal boron nitride powder, it has excellent extensibility, and a cosmetic layer formed using the cosmetic can have excellent transparency and luster. Effect of the Invention
[0015] According to the present disclosure, it is possible to provide a hexagonal boron nitride powder for cosmetics which has excellent elongation when used as a cosmetic and gives the cosmetic layer excellent transparency and luster. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, embodiments of the present disclosure will be described. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents.
[0017] Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0018] One embodiment of the hexagonal boron nitride powder for cosmetics contains primary particles of hexagonal boron nitride, and the primary particles have an aspect ratio of 25 or less and an oil absorption of 50 to 90 mL / 100 g.
[0019] The shape of the primary particles of hexagonal boron nitride is preferably a scale shape in order to improve the slipperiness, extensibility, and hiding power. The upper limit of the aspect ratio of the primary particles of hexagonal boron nitride may be, for example, 22 or less, 20 or less, 19 or less, or 18 or less. When the upper limit of the aspect ratio is within the above range, the primary particles have an appropriate thickness, and cracking of the primary particles can be suppressed, thereby suppressing an increase in the amount of boron dissolved. In addition, it is possible to prevent light reflection and provide an appropriate sense of transparency. The lower limit of the aspect ratio of the primary particles may be, for example, 5 or more, 7 or more, 10 or more, 12 or more, or 15 or more. When the lower limit of the aspect ratio is within the above range, the extensibility of the cosmetic obtained when used as an extender pigment for a cosmetic can be further improved. When the lower limit of the aspect ratio is within the above range, when the hexagonal boron nitride powder is used as an extender pigment for a cosmetic, the cosmetic obtained can exhibit excellent hiding power (covering power). The aspect ratio of the primary particles of the hexagonal boron nitride may be adjusted within the above range, for example, 5-22, 10-22, or 15-22.
[0020] The aspect ratio of a primary particle is represented by the ratio ((major axis) / (minor axis)) of the longest point (major axis) of a particle to the shortest point (minor axis). In the case of hexagonal boron nitride, the primary particles are scaly particles, so the thickness of the scaly particles is the shortest point (minor axis) of the particle. In other words, the "aspect ratio of a primary particle" in this specification means a value obtained by measuring the particle major axis from an electron microscope image of a primary particle of hexagonal boron nitride, measuring the particle thickness from a cross-sectional photograph image, and calculating the above ratio from the measured results. In other words, the aspect ratio of a primary particle of hexagonal boron nitride is a value represented by (major axis) / (thickness) of a primary particle of hexagonal boron nitride.
[0021] When measuring the aspect ratio of a scaly particle such as hexagonal boron nitride, for example, an error is likely to occur when a particle image taken by an electron microscope is directly analyzed (for example, if the primary particle is tilted, an error occurs in the short side (corresponding to the particle thickness and the particle short diameter)), making accurate measurement difficult. Therefore, the aspect ratio of hexagonal boron nitride in this specification is calculated using the particle long diameter and particle short diameter of the primary particle of hexagonal boron nitride obtained by measurement in accordance with the method shown below. First, the particle long diameter of the primary particle of hexagonal boron nitride is measured by photographing hexagonal boron nitride powder with a scanning electron microscope, importing the obtained particle image into image analysis software, and measuring the long side of the primary particle from the obtained photograph. Next, the particle short diameter of the primary particle of hexagonal boron nitride is measured. First, 3 g of boron nitride powder is molded into a disk shape (diameter: 30 mmφ) using a press molding machine at a pressure of 5 MPa, and the molded body obtained is embedded in resin and then cross-sectional milling is performed in a direction parallel to the direction of pressure application to prepare a sample with an exposed cross section of the boron nitride particles. Since the primary particles of boron nitride are oriented in one direction by press molding, measurement errors of the short side due to the inclination of the primary particles are suppressed. This cross section is photographed using a scanning electron microscope, and the obtained particle image is imported into image analysis software, and the short side is measured from the obtained photograph. Both the long diameter and the short diameter of the particles are measured for 100 randomly selected primary particles, and the arithmetic average value is used.
[0022] The upper limit of the oil absorption of the hexagonal boron nitride powder may be, for example, 88 mL / 100 g or less, 86 mL / 100 g or less, 85 mL / 100 g or less, or 80 mL / 100 g or less. When the hexagonal boron nitride powder having an upper limit of the oil absorption within the above range is used as a body pigment for cosmetics, it can maintain dispersibility with oils, so that there is no need to perform surface treatment or the like to mix with oils when formulating, and it is possible to easily formulate the powder while maintaining the inherent tactile feel of hexagonal boron nitride. The lower limit of the oil absorption of the hexagonal boron nitride powder may be, for example, 55 mL / 100 g or more, 60 mL / 100 g or more, 65 mL / 100 g or more, 70 mL / 100 g or more, or 75 mL / 100 g or more. By having the lower limit of the oil absorption within the above range, it is possible to suppress the affinity with sebum and prevent makeup from being ruined by sebum. The oil absorption of the hexagonal boron nitride powder can be controlled, for example, by adjusting the BET specific surface area of the primary particles, and can be controlled by adjusting conditions such as the heating temperature during the production of the hexagonal boron nitride powder. The oil absorption of the hexagonal boron nitride powder may be adjusted within the above-mentioned range, and may be, for example, 50 to 88 mL / 100 g, 60 to 88 mL / 100 g, or 70 to 86 mL / 100 g.
[0023] In this specification, "oil absorption" is a value measured in accordance with the method described in JIS K 5101-13-1:2004 "Testing methods for pigments - Part 13: Oil absorption - Section 1: Refined linseed oil method". The oil absorption corresponds to the amount of oil when the sample becomes pasty when oil is dropped onto the sample. For example, a sample with high lipophilicity will have a low oil absorption because it becomes pasty with a small amount of oil, while a sample with high hydrophilicity (a sample with low affinity for oil) will have a high oil absorption because it requires a large amount of oil to make it into a paste.
[0024] The lower limit of the BET specific surface area of the hexagonal boron nitride powder is, for example, 1.5 m 2 / g or more, 1.8m 2 / g or more, 1.9m 2 / g or more, 2.0m 2 / g or more, 2.3m 2 / g or more, or 2.5m 2 / g or more. When the lower limit of the BET specific surface area is within the above range, it is possible to suppress an excessively strong glossiness of the cosmetic layer when the hexagonal boron nitride powder is used as a raw material for a cosmetic. The upper limit of the BET specific surface area of the hexagonal boron nitride powder is, for example, 5.0 m 2 / g or less, 4.0m 2 / g or less, or 3.0m 2 / g or less. By setting the upper limit of the BET specific surface area within the above range, the amount of boron eluted from the hexagonal boron nitride powder can be reduced, while providing the decorative layer with a suitable gloss and a more preferable glossy feel. The BET specific surface area may be adjusted within the above range, for example, 1.5 to 5.0 m 2 The BET specific surface area of hexagonal boron nitride can be controlled, for example, by adjusting conditions such as the heating temperature during the production of hexagonal boron nitride powder.
[0025] In this specification, the "BET specific surface area" is a value measured by the BET single-point method using nitrogen gas in accordance with the method described in JIS Z 8830:2013 "Method for measuring specific surface area of powder (solid) by gas adsorption."
[0026] The upper limit of the tap density of the hexagonal boron nitride powder is, for example, 0.35 g / cm 3 Below, 0.30g / cm 3 Below 0.25g / cm 3 or less than 0.23g / cm 3 If the upper limit of the tap density is within the above range, the density is low, so resistance is low when applied, and the hexagonal boron nitride powder can be spread thinly while fitting to the skin with light force, making it possible to impart a superior sense of transparency to the cosmetic layer. The lower limit of the tap density of the hexagonal boron nitride powder is usually 0.02 g / cm. 3 or more, or 0.05g / cm 3 For example, 0.08 g / cm 3 More than 0.10g / cm 3 More than 0.10g / cm 3 More than 0.15g / cm 3 or more than 0.20g / cm3 If the lower limit of the tap density is within the above range, handling during production and mixing with oils for formulation will be facilitated. The tap density of the hexagonal boron nitride powder may be adjusted within the above range, for example, 0.02 to 0.35 g / cm. 3 , 0.05~0.35g / cm 3 , or 0.20 to 0.35 g / cm 3 It may be.
[0027] The tap density in this specification means a value determined in accordance with JIS R 1628:1997 "Method of measuring bulk density of fine ceramic powders". A commercially available device can be used for the measurement. Specifically, the measurement is performed under the conditions described in the examples.
[0028] The upper limit of the total oxygen content of the hexagonal boron nitride powder may be, for example, 0.20% by mass or less, 0.15% by mass or less, 0.12% by mass or less, or 0.10% by mass or less. By the upper limit of the total oxygen content being within the above range, adhesion and aggregation between hexagonal boron nitride particles can be reduced, and extensibility can be further improved. The lower limit of the total oxygen content of the hexagonal boron nitride powder may be, for example, 0.01% by mass or more, 0.02% by mass or more, 0.03% by mass or more, 0.04% by mass or more, or 0.05% by mass or more. By the lower limit of the total oxygen content being within the above range, dispersibility in polar solvents can be further improved. Therefore, when the hexagonal boron nitride powder is used as an extender pigment to prepare a cosmetic, it becomes easy to mix with other pigments, etc., and the cosmetic can be produced smoothly. The total oxygen content may be adjusted within the above range, for example, 0.01 to 0.20 mass%, or 0.01 to 0.10 mass%. The total oxygen content can be controlled, for example, by adjusting conditions such as the heating temperature during the production of the hexagonal boron nitride powder.
[0029] In this specification, the term "total oxygen content" refers to the total oxygen content of the hexagonal boron nitride powder. The total oxygen content can be determined by the following procedure. The oxygen and nitrogen content of the hexagonal boron nitride powder is analyzed using an oxygen / nitrogen analyzer. The measurement sample is heated in a helium gas atmosphere from 20°C to about 2500°C, that is, above the reactive decomposition temperature of boron nitride. The oxygen that is desorbed with the temperature increase is detected. At the beginning of the temperature increase, oxygen bonded to the surface of the hexagonal boron nitride powder is desorbed. The amount of surface oxygen is determined by quantifying the amount of desorbed oxygen. After that, when the temperature reaches approximately 1400°C, the hexagonal boron nitride begins to decompose. The start of decomposition of hexagonal boron nitride can be grasped by the start of detection of nitrogen. When hexagonal boron nitride begins to decompose, oxygen inside the hexagonal boron nitride particles is desorbed. The amount of internal oxygen is determined by quantifying the amount of oxygen that is desorbed at this stage. The sum of the surface oxygen amount and the internal oxygen amount thus obtained is the total oxygen amount.
[0030] In the hexagonal boron nitride powder, the lower limit of the average particle size may be, for example, 4 μm or more, 5 μm or more, 7 μm or more, or 8 μm or more. When the lower limit of the average particle size is within the above range, when the hexagonal boron nitride powder is used as a body pigment for cosmetics, the resulting cosmetics can have improved extensibility. The upper limit of the average particle size may be, for example, 19 μm or less, 18 μm or less, 17 μm or less, or 16 μm or less. When the upper limit of the average particle size is within the above range, it is possible to suppress an excessively strong glossy feeling. The average particle size may be adjusted within the above range, and may be, for example, 4 to 19 μm. The average particle size can be controlled, for example, by adjusting conditions such as the heating temperature during the production of the hexagonal boron nitride powder.
[0031] The average particle size in this specification means the 50% cumulative diameter (median diameter) in the cumulative particle size distribution based on volume. In this specification, the "50% cumulative diameter in the cumulative particle size distribution based on volume" means the particle size (D50) at which the cumulative value in the cumulative particle size distribution based on volume becomes 50% when the particle size distribution of the hexagonal boron nitride powder is measured by the laser diffraction scattering method. The laser diffraction scattering method is measured in accordance with the method described in JIS Z 8825:2013 "Particle size analysis - laser diffraction and scattering method". For the measurement, a laser diffraction scattering particle size distribution measuring device or the like can be used. For the laser diffraction scattering particle size distribution measuring device, for example, "LS-13 320" (product name) manufactured by Beckman Coulter, Inc. can be used.
[0032] The amount of eluted boron in the hexagonal boron nitride powder is sufficiently reduced. The amount of eluted boron in the hexagonal boron nitride powder can be, for example, 20 mass ppm or less, 15 mass ppm or less, 10 mass ppm or less, 8 mass ppm or less, or 6 mass ppm or less. By reducing the amount of eluted boron in the hexagonal boron nitride powder, irritation to the skin can be reduced, making the hexagonal boron nitride powder more useful as an extender pigment for use in cosmetics.
[0033] In this specification, the "amount of dissolved boron" refers to a value measured in accordance with the description of the 2006 Standards for Quasi-Drug Ingredients.
[0034] The above-mentioned hexagonal boron nitride powder for cosmetics can be suitably used as a body pigment and can be considered as a raw material for cosmetics. Therefore, the above-mentioned hexagonal boron nitride powder can be considered as a body pigment for cosmetics. The present disclosure can also provide a cosmetic containing the above-mentioned hexagonal boron nitride powder.
[0035] Examples of the cosmetic include foundation (powder foundation, liquid foundation, cream foundation), face powder, point makeup, eye shadow, eyeliner, nail polish, lipstick, blusher, and mascara. Of these, hexagonal boron nitride powder is particularly well suited for foundation and eye shadow. The content of the hexagonal boron nitride powder in the cosmetic is, for example, 0.1 to 70 mass %. The cosmetic can be manufactured by a known method. The manufacturing method for the cosmetic includes, for example, a step of blending and mixing the hexagonal boron nitride powder with other raw materials.
[0036] The above-mentioned hexagonal boron nitride powder for cosmetics can be manufactured, for example, by the following method. One example of a method for manufacturing hexagonal boron nitride powder for cosmetics includes a step of firing a raw material composition containing a boron-containing compound containing boric acid and a nitrogen-containing compound containing melamine at 600 to 1300 ° C. in an atmosphere containing at least one of an inert gas and ammonia gas to obtain a calcined product containing at least one selected from the group consisting of low-crystalline boron nitride and amorphous boron nitride (hereinafter also referred to as the calcination step), a step of firing a mixed powder containing the calcined product and an auxiliary at a temperature of 1500 to 1750 ° C. in an atmosphere containing at least one of an inert gas and ammonia gas to obtain a fired product (hereinafter also referred to as the firing step), a step of pulverizing, washing and drying the fired product to obtain a dry powder (hereinafter also referred to as the purification step), and a step of heat-treating the dry powder at a temperature of 1900 ° C. or higher in an atmosphere containing at least one of an inert gas and ammonia gas (annealing step).
[0037] The above-mentioned baking step may be repeated multiple times (hereinafter, each step is referred to as the first baking step, the second baking step, etc., in that order). When the baking step is repeated multiple times, the baked product obtained in each baking step may be pulverized. By pulverizing the baked product, the melamine and the like in the raw material composition can be sufficiently consumed in the second baking step and subsequent baking steps. The pulverization step may also include washing and drying the powder obtained by pulverization to obtain a dry powder.
[0038] The boron-containing compound is a compound having a boron atom as a constituent element. The boron-containing compound may further contain, for example, boron oxide and borax in addition to boric acid. The nitrogen-containing compound is a compound having a nitrogen atom as a constituent element, and may be an organic compound. The nitrogen-containing compound may further contain, for example, dicyandiamide and urea in addition to melamine. The raw material composition may contain components other than the above compounds. For example, it may contain carbonates such as lithium carbonate and sodium carbonate as a calcination auxiliary. It may also contain a reducing substance such as carbon.
[0039] In the raw material composition, the compounding ratio of the boron-containing compound and the nitrogen-containing compound may be adjusted based on the molar ratio of boron atoms to nitrogen atoms, and may be, for example, boron atoms:nitrogen atoms=2:8 to 8:2, or 2.5:7.5 to 7.5:2.5.
[0040] In the calcination step, the raw material composition is calcined, for example, using an electric furnace to obtain a calcined product. The calcination step is performed in an atmosphere containing at least one of an inert gas and an ammonia gas. Examples of the inert gas include nitrogen gas and a rare gas. Examples of the rare gas include helium gas and argon gas. The calcination step may be performed in a mixed gas atmosphere of an inert gas and an ammonia gas. The calcination temperature may be, for example, 600 to 1300°C, 800 to 1200°C, or 900 to 1100°C. The calcination time may be, for example, 0.5 to 5.0 hours, or 1.0 to 4.0 hours.
[0041] The calcined product obtained by calcination contains at least one selected from the group consisting of low-crystalline boron nitride and amorphous boron nitride, and may further contain hexagonal boron nitride. The calcination step allows the reaction of boron nitride to proceed at a lower temperature than the firing step described below. By lowering the calcination temperature, grain growth can be suppressed, and the average grain size of the finally obtained hexagonal boron nitride powder can be reduced. In addition, by lowering the calcination temperature, grain growth can be suppressed, and the BET specific surface area of the hexagonal boron nitride powder can be increased.
[0042] Next, in the firing step, the calcined product obtained as described above is mixed with an auxiliary to prepare a mixed powder, which is then fired. In the firing step, in the presence of the auxiliary, the raw material composition is sufficiently consumed while the production and crystallization of boron nitride proceeds. This increases the crystallinity of the boron nitride contained in the calcined product, allowing it to form hexagonal boron nitride. The mixed powder may further contain boric acid.
[0043] Examples of the auxiliary include borates such as sodium borate, and carbonates such as sodium carbonate, calcium carbonate, and lithium carbonate. The auxiliary preferably contains sodium carbonate. The amount of the auxiliary to be blended relative to 100 parts by mass of the calcined product containing boron nitride is 2 parts by mass or more and less than 20 parts by mass, and may be, for example, 3 to 10 parts by mass, or 3 to 7 parts by mass.
[0044] In the firing step, the mixed powder is fired, for example, using an electric furnace to obtain a fired product. The firing step is performed in an atmosphere containing at least one of an inert gas and ammonia gas. Examples of the inert gas include nitrogen gas and rare gas. Examples of the rare gas include helium gas and argon gas. The firing step may be performed in a mixed gas atmosphere containing an inert gas and ammonia gas.
[0045] The firing temperature is 1500 to 1750° C. This firing temperature may be, for example, 1550 to 1850° C., or 1600 to 1750° C. The firing time may be, for example, 0.5 to 5 hours, or 1 to 4 hours.
[0046] In this specification, the firing time, heating time, calcination time, etc. refer to the time (retention time) during which the temperature of the environment surrounding the object is maintained at a specified temperature after the temperature has reached that temperature.
[0047] By setting the firing temperature relatively high, the raw material composition is consumed, and amorphous carbon and graphite generated by the reaction of the raw material composition are consumed, and the generation and crystallization of hexagonal boron nitride can be sufficiently promoted. By reducing the amount of raw materials containing carbon, such as melamine, in the raw material composition, the quality of the obtained hexagonal boron nitride powder can be further improved. The same tendency is also observed by extending the firing time. On the other hand, if the firing temperature is too high, the crystal growth of hexagonal boron nitride tends to proceed too much, making fine pulverization difficult. The same tendency is also observed when the firing time is too long.
[0048] The fired product obtained in the firing step may be pulverized using, for example, a pulverizer. As the pulverizer, for example, an impact pulverizer (pulverizer) or the like may be used. As the impact pulverizer, for example, an impact type screen type fine pulverizer or the like that can adjust the particle size of the pulverized product by a screen can be suitably used. The mesh size of the screen may be, for example, 0.1 to 1 mm, or 1 to 3 mm.
[0049] In the pulverization step, the sintered product is pulverized to adjust the particle size. By adjusting the particle size, the efficiency of the subsequent annealing step can be improved. The pulverized product obtained by pulverizing the sintered product may contain impurities other than hexagonal boron nitride. Therefore, a treatment (purification treatment) for reducing the impurities may be performed before the annealing step. Examples of impurities include remaining raw materials and auxiliary agents, as well as water-soluble boron compounds. The purification treatment reduces the amount of such impurities, for example, by washing. After washing, the solid-liquid separation is performed and the product is dried to obtain a dry powder. By performing the pulverization step and purification treatment before the annealing step, a powder or dry powder with a reduced content of auxiliary agents and the like compared to the sintered product is prepared, and the powder or dry powder is annealed to further reduce the amount of oxygen while suppressing grain growth.
[0050] Examples of the cleaning liquid used for cleaning include an aqueous solution containing water and an acidic substance, an organic solvent, and a mixture of an organic solvent and water. In order to avoid secondary contamination of impurities, water having an electrical conductivity of 1 mS / m or less may be used. Examples of the aqueous solution containing an acidic substance include inorganic acids such as hydrochloric acid and nitric acid. Examples of the organic solvent include water-soluble organic solvents such as methanol, ethanol, propanol, isopropyl alcohol, and acetone. There is no particular limitation on the cleaning method, and for example, the pulverized material may be immersed in the cleaning liquid and stirred to clean, or the pulverized material may be sprayed with the cleaning liquid to clean.
[0051] After the washing is completed, the washing liquid may be separated into solid and liquid using a decanter, a suction filter, a pressure filter, a rotary filter, a sedimentation separator, or a combination of these. The separated solid may be dried in a conventional dryer to obtain a dry powder. Examples of the dryer include a shelf dryer, a fluidized bed dryer, a spray dryer, a rotary dryer, a belt dryer, and combinations thereof. After drying, classification may be performed, for example, using a sieve to remove coarse particles.
[0052] In the annealing step, the pulverized product or dried powder of the fired product is heat-treated, for example, using an electric furnace. The annealing step is performed in an atmosphere containing at least one of an inert gas and ammonia gas. Examples of the inert gas include nitrogen gas and rare gas. The rare gas may be, for example, helium gas and argon gas. The calcination step may be performed in a mixed gas atmosphere containing an inert gas and ammonia gas. The temperature of the heat treatment in the annealing step is 1900°C or higher, but may be 1950°C or higher or 2000°C or higher from the viewpoint of sufficiently reducing the amount of oxygen. By performing the annealing step, oxygen present as functional groups on the surface of the particles can be scattered, thereby reducing the amount of oxygen.
[0053] From the viewpoint of suppressing particle growth, the temperature of the heat treatment in the annealing step may be 2200° C. or less, or 2100° C. or less. From the viewpoint of sufficiently reducing the amount of oxygen and suppressing particle growth, the heating time in the annealing step may be, for example, 0.5 to 5.0 hours, or 1.0 to 4.0 hours.
[0054] Although several embodiments have been described above, the descriptions of the embodiments can be applied to each other with respect to common configurations. Furthermore, the present disclosure is not limited to the above-described embodiments. EXAMPLES
[0055] The present disclosure will be described in more detail with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.
[0056] Example 1 [Production of hexagonal boron nitride powder] <Pre-firing process> 100.0 g of boric acid powder (purity: 99.8% by mass or more, manufactured by Kanto Chemical Co., Ltd.) and 90.0 g of melamine powder (purity: 99.0% by mass or more, manufactured by Wako Pure Chemical Industries, Ltd.) were mixed for 10 minutes using an alumina mortar to obtain a mixed raw material. The dried mixed raw material was placed in a container made of hexagonal boron nitride and placed in an electric furnace. While circulating nitrogen gas in the electric furnace, the temperature was raised from room temperature to 1000°C at a rate of 10°C / min. After holding at 1000°C for 2 hours, heating was stopped and the material was allowed to cool naturally. When the temperature reached 100°C or less, the electric furnace was opened. In this way, a calcined product containing low-crystalline boron nitride was obtained.
[0057] <Firing process> 5.0 g of sodium carbonate (purity: 99.5 mass% or more) was added as an auxiliary agent to 100.0 g of the calcined product, and mixed for 10 minutes using an alumina mortar. The mixture was placed in the electric furnace described above. While circulating nitrogen gas in the electric furnace, the temperature was raised from room temperature to 1600°C at a rate of 10°C / min. After maintaining the firing temperature of 1600°C for 4 hours, heating was stopped and the product was allowed to cool naturally. When the temperature reached 100°C or less, the electric furnace was opened. The obtained fired product was collected and pulverized in an alumina mortar for 3 minutes to obtain a coarse powder containing hexagonal boron nitride.
[0058] <Purification process> In order to reduce impurities contained in the coarse powder, 30 g of the coarse powder was added to 500 g of dilute nitric acid (nitric acid concentration: 5% by mass) and stirred at room temperature for 60 minutes. After stirring, the solid-liquid separation was performed by suction filtration, and the filtrate was washed by replacing it with water (water with an electrical conductivity of 1 mS / m) until it became neutral. After washing, the mixture was dried at 120°C for 3 hours using a dryer to obtain a dry powder.
[0059] <Annealing process> The dried powder was placed in the electric furnace described above. The temperature was raised from room temperature to 2000°C at a rate of 10°C / min while circulating nitrogen gas in the electric furnace. After holding at 2000°C for 4 hours, heating was stopped and the material was allowed to cool naturally. When the temperature dropped below 100°C, the electric furnace was opened.
[0060] <Crushing process> The obtained fired product was collected and pulverized in an alumina mortar for 3 minutes. From the obtained dry powder, coarse powder was removed using an ultrasonic vibration sieve (KFS-10000, manufactured by Kowa Kogyosho, mesh size 250 μm) to obtain the hexagonal boron nitride powder of Example 1.
[0061] [Physical properties measurement of hexagonal boron nitride powder] The primary particle aspect ratio, oil absorption, primary particle BET specific surface area, tap density, and total oxygen content of the hexagonal boron nitride powder prepared in Example 1 were evaluated by the methods described below. The results are shown in Table 1.
[0062] <Aspect ratio> The aspect ratio of the primary particles of hexagonal boron nitride was determined by calculating the ratio of the long axis to the short axis (long axis / short axis) using the long axis and short axis of the primary particles of hexagonal boron nitride obtained by the method described below. Regarding the long axis of the particles, instead of a molded body, hexagonal boron nitride powder was placed on carbon tape on a sample stage for an electron microscope, and the sample after removing excess powder with air spray or the like was photographed with a scanning electron microscope (manufactured by JEOL Ltd., product name: JSM-6010LA), and the obtained particle image was imported into image analysis software (manufactured by Mountec Co., Ltd., product name: Mac-View), and the long side (corresponding to the long axis of the particle) was calculated from the obtained photograph, and the aspect ratio (long axis / short axis) was calculated together with the short axis. Regarding the particle minor diameter, 3 g of hexagonal boron nitride powder was molded into a disk shape (diameter: 30 mmφ) at a pressure of 5 MPa using a press molding machine (Rigaku Corporation, product name: BRE-32), and the molded body obtained was embedded in resin (GATAN Corporation, product name: G2 epoxy). Next, a cross-sectional milling process was performed in the direction parallel to the pressure applied to prepare a sample with an exposed cross section of the hexagonal boron nitride particle. This cross section was photographed using a scanning electron microscope (JEOL Ltd., product name: JSM-6010LA), and the obtained particle image was imported into image analysis software (Mountec Corporation, product name: Mac-View), and the short side of the rectangular particle (corresponding to the particle thickness, the particle minor diameter) was measured from the obtained photograph. Both the particle major diameter and the particle minor diameter were measured for 100 randomly selected primary particles, and the arithmetic average value was used.
[0063] <Oil absorption amount> The oil absorption of the hexagonal boron nitride powder was measured in accordance with the method described in JIS K 5101-13-1:2004 "Test methods for pigments - Part 13: Oil absorption - Section 1: Refined linseed oil method."
[0064] <BET specific surface area of primary particles> The BET specific surface area of the primary particles of hexagonal boron nitride was measured by the BET single-point method using nitrogen gas in accordance with the method described in JIS Z 8830:2013 "Method for measuring specific surface area of powder (solid) by gas adsorption."
[0065] <Tap density> Tap density is measured according to JIS R 1628:1997 "Method of measuring bulk density of fine ceramic powders" by measuring the object to be measured at 100 cm 3 The mixture was filled into a special container and tapped under the conditions of a tapping time of 180 seconds, tapping count of 180 times, and tap lift of 18 mm, after which the bulk density was measured and the obtained value was taken as the tapped density.
[0066] <Total oxygen amount> The total oxygen content of the primary particles of hexagonal boron nitride was measured using an oxygen and nitrogen simultaneous analyzer (EMGA-920, manufactured by Horiba, Ltd.) Specifically, the measurements were performed while heating the hexagonal boron nitride powder from 20°C to 2500°C in a helium atmosphere.
[0067] [Evaluation of hexagonal boron nitride powder as a cosmetic ingredient] The hexagonal boron nitride powder prepared in Example 1 was evaluated for its spreadability when used as a cosmetic material, as well as the transparency and luster of a cosmetic layer formed from the cosmetic material, by the methods described below.
[0068] <Evaluation of elongation> 0.2 g of hexagonal boron nitride powder was placed over a width of 10 mm on one end of the artificial skin (length x width = 10 mm x 50 mm). A spatula was used to spread the hexagonal boron nitride powder along the length so as to smear it onto the surface of the artificial skin. Image analysis was performed using commercially available image analysis software (WinROOF) to determine the ratio of the applied area of the hexagonal boron nitride powder to the total area of the artificial skin. The larger this area ratio, the better the extensibility. From the results obtained, the extensibility was evaluated according to the following criteria. The evaluation results are shown in Table 1. A: The above coating area ratio is 95% or more. B: The proportion of the above coating area is 80% or more and less than 95%. C: The proportion of the above-mentioned coating area is 70% or more and less than 80%. D: The proportion of the above-mentioned coating area is 60% or more and less than 70%. E: The proportion of the above coating area is 40% or more and less than 60%. F: The proportion of the above-mentioned coating area is less than 40%.
[0069] <Evaluation of transparency and luster of cosmetic layer> A sensory evaluation was performed on the transparency and luster of the cosmetic layer. The evaluation was performed by 10 randomly selected expert panelists. The evaluation items were the transparency and luster of the cosmetic layer, and the transparency and luster of the cosmetic layer (reference cosmetic layer) formed using the hexagonal boron nitride powder obtained in Example 2 were each rated on a 5-point scale: "3" for transparency and luster superior to the reference cosmetic layer, "4" for transparency and luster even superior to the reference cosmetic layer, "5" for transparency and luster inferior to the reference cosmetic layer, "2" for transparency and luster inferior to the reference cosmetic layer, and "1" for transparency and luster superior to the reference cosmetic layer. The arithmetic mean value of the evaluation results of the 10 expert panelists was used as the evaluation result of the cosmetic layer to be evaluated, and was judged based on the following criteria. The results are shown in Table 1. The difference between the "transparency" and the reference cosmetic layer was evaluated on a scale of whether the finished cosmetic layer felt integrated with the skin without feeling thick, and the difference between the "luster" and the reference cosmetic layer was evaluated on a scale of whether the finished cosmetic layer felt luster. A: The above evaluation result is 4.5 or higher. B: The above evaluation result is 3.5 or more and less than 4.5. C: The above evaluation result is 2.5 or more and less than 3.5. D: The above evaluation result is 1.5 or more and less than 2.5. E: The above evaluation result is less than 1.5.
[0070] Comparative Example 1 Hexagonal boron nitride powder was prepared in the same manner as in Example 1, except that the firing temperature in the firing step was 1800° C. Then, the hexagonal boron nitride powder was measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0071] Example 2 Hexagonal boron nitride powder was prepared in the same manner as in Example 1, except that the firing temperature in the annealing step was set to 1800° C. Then, the hexagonal boron nitride powder was measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0072] Comparative Example 2 Except for not performing the annealing step, hexagonal boron nitride powder was prepared in the same manner as in Example 1. Then, the hexagonal boron nitride powder was measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0073] Comparative Example 3 Except for changing the amount of sodium carbonate added in the firing step to 20 g, hexagonal boron nitride powder was prepared in the same manner as in Example 1. Then, the hexagonal boron nitride powder was measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0074] [Table 1] [Industrial Applicability]
[0075] According to the present disclosure, an object is to provide a hexagonal boron nitride powder for cosmetics which has excellent elongation when used as a cosmetic and gives the cosmetic layer excellent transparency and luster.
Claims
1. Contains primary particles of hexagonal boron nitride, The primary particles have a scale-like shape, The aspect ratio of the primary particles is 5 to 22; The total oxygen content is 0.02 to 0.08 mass%; The oil absorption is 78 to 85 mL / 100 g. The BET specific surface area is 2.4 to 2.8 m 2 / g; A hexagonal boron nitride powder for use in cosmetics, having a tap density of 0.20 g / cm 3 or more.
2. Tap density is 0.35 g / cm 3 The hexagonal boron nitride powder for cosmetics according to claim 1, which is as follows:
3. A cosmetic comprising the hexagonal boron nitride powder for cosmetics according to claim 1 or 2.
Citation Information
Patent Citations
High oil absorptive boron nitride powder excellent in heat release and cosmetics
JP2014094878A
Hexagonal boron nitride powder and method for producing the same
JP2015212217A
Hexagonal boron nitride powder and cosmetics
JP2018108970A
Hexagonal crystal boron nitride powder and cosmetic
JP2019043792A
Hexagonal boron nitride powder and method for producing the same, and cosmetics and method for producing the same
JP2021116205A